Efficacy and Safety of Combined Surgeries including Intraocular Direct Cyclophotocoagulation with a 532 nm Laser to Treat Advanced Neovascular Glaucoma. (8th July 2021) - Chen, Xiaomin; Zheng, Tian; Zeng, Wen; Fu, Xia; Wang, Shun; Zeng, Weijuan; Ke, Min
Abstract : Purpose . The purpose of this study was to assess the efficacy and safety of intraocular direct cyclophotocoagulation (IDCP) using a 532 nm laser with combination treatment in reducing intraocular pressure (IOP) for patients with advanced neovascular glaucoma (NVG) with angle closure. In addition, we sought to determine the success rate and frequency of complications and explore an optimized solution to reduce the number of topical medications and the pain of patients. Methods . A retrospective case note review of all patients undergoing combined treatment including IVR, phaco, PPV, PRP, and IDCP from January 2017 to June 2018. Results . In total, 24 consecutive patients (25 eyes) were reviewed. The mean IOP was significantly decreased from 42.2 ± 8.5 mmHg preoperatively to 15.56 ± 2.0 mmHg (P < 0.0001 ), and no neovascularization of the iris (NVI) reoccurred at month 18. The number of medications used was reduced from 2.72 ± 0.45 preoperatively to 0.87 ± 0.40 at month 18 (P < 0.0001 ). Conclusions . During 18 months of follow-up, the combined treatments were safe and had a significant IOP-lowering effect. This study provides a new method of performing IDCP with a 532 nm laser, allowing for the use of internal cyclophotocoagulation without extra equipment.